Julio César Arana, Barón del caucho - (:unkn) unknown (Universidad Nacional de Río Cuarto. Editorial UNIRIO. Cultura en Red, 2020)
From the figure of Julio César Arana, Barón del rubber, a series of events occurred in Putumayo during the Rubber era (1880- 1914), and the actions of civilians and Augustinian missionaries who arrived in Iquitos in 1901. In this work, we try to show how the local hegemonic power influenced the national level, through the figure of the Lord of rubber mentioned above, and that the rubber extraction industry is a story of blood and humiliations that the indigenous people have suffered in pursuit of rebuild the national economy.

A partir de la figura de Julio César Arana, Barón del caucho, se presentan una serie de hechos ocurridos en el Putumayo en la época del Caucho (1880-1914), y el accionar de civiles y de los misioneros agustinos quienes arribaron a Iquitos en 1901. En este trabajo, pretendemos mostrar cómo el poder hegemónico local incidió a nivel nacional, a través de la figura del Señor del caucho antes mencionado, y que la industria extractiva del caucho es una historia de sangre y vejámenes que han sufrido los indígenas en pos de reconstruir la economía nacional.
Fil: Fernández, María Victoria. Instituto Superior del Profesorado "Dr. Joaquín V. González"; Argentina. Centro de Investigaciones Precolombinas; Argentina.
Keywords: Peruvian amazon; Rubber season; Rubber barons; Augustinian missionaries; Amazonía peruana; Época del caucho; Barones del caucho; Misioneros agustinos; Arqueología